Clonality increases with snow depth in the arctic dwarf shrub Empetrum hermaphroditum - Bienau, M.J.; Eckstein, R.L.; Otte, A.; Durka, Walter (American Journal of Botany, 2016)
PREMISE OF THE STUDY: Vegetative reproduction and spread through clonal growth plays an important role in arctic-alpine ecosystems with short cool growing seasons. Local variation in winter snow accumulation leads to discrete habitat types that may provide divergent conditions for sexual and vegetative reproduction. Therefore, we studied variation in clonal structure of a dominant, evergreen, dwarf shrub (Empetrum nigrum s.l. with the two taxa E. nigrum L. s.s. and E. hermaphroditum Hagerup) along a snow cover gradient and compared clonal diversity and spatial genetic structure between habitats. METHODS: We studied 374 individual shoots using 105 polymorphic AFLP markers and analyses based on hierarchical clustering, clonal diversity indices, and small-scale spatial genetic structure with pairwise kinship coefficient. We used two approaches to define a threshold of genotypic distance between two samples that are considered the same clone. Clonality was examined among three habitats (exposed ridges, sheltered depressions, birch forest) differing in snow conditions replicated in four study regions in Norway and Sweden. KEY RESULTS: Clonality of E. hermaphroditum differed between habitats with an increase in clonal diversity with decreasing snow depth. Small-scale spatial genetic structure increased with decreasing clonal diversity and increasing clone size. In three study regions, E. hermaphroditum was the only species, whereas in one region E. nigrum also occurred, largely confined to exposed ridges. CONCLUSIONS: Our results demonstrated that snow cover in conjunction with associated habitat conditions plays an important role for the mode of propagation of the dwarf shrub E. hermaphroditum.